PERAN KEPALA SEKOLAH DALAM PENGEMBANGAN SUMBER DAYA MANUSIA (SDM) GURU - Septian, Dwi; Kurniawan, Gilang Dwi; Fakhrin, Edi; Aslamiah, Aslamiah; Cinantya, Celia (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The role of the principal is crucial in ensuring the continuity of the school's daily operations as well as in leading the development of human resources, especially teachers. Principals not only perform administrative functions, but also act as managers, leaders and change agents who create a conducive learning environment. In the context of education that is increasingly influenced by the demands of globalization, principals are required to be visionary leaders who can inspire and transform educators. This study aims to explore the principal's responsibilities in developing teacher competencies, the strategies used, the obstacles faced, and the solutions that can be applied to improve the quality of education. The approach used is descriptive qualitative with a literature review method, including analysis of books, journal articles, case studies and previous research. The results of the study show that effective principal leadership can improve teachers' professionalism, strengthen the quality of the learning process, and promote students' academic achievement and character development. This article highlights the importance of innovation and collaboration between principals and teachers in optimizing human resource potential. The role of principals as innovative leaders and professional developers of teachers is key in maintaining and improving education standards that are sustainable and relevant to the challenges of the times.